Handbuch der Tonstudiotechnik. - Dickreiter, Michael (K.G. Saur, 2008)
This Handbook has been a standard work for professional sound studio recording engineersfor more than 30 years. The two volumes of the 7th edition, published by the ARD. ZDF medienakademie (German Public Broadcastingmedia academy) take account of all relevant developments in the field. Volume 1 presents the basic physical and technical principles involved and also covers analogue studio recording. Volume 2 then gives a significantly more comprehensive account of present-day digital technologies and other modern developments. 2 volumes covering the main features of analogue and digital sound stu.